KONSEP HUBUNGAN TOTAL (TOTAL RELATIONSHIP CONCEPT) DALAM PEMBERIAN KREDIT OLEH BANK KEPADA NASABAH - Prabowo, Marcellino Mukti; Suherman, Suherman (Kertha Semaya : Journal Ilmu Hukum, 2024)
This research aims to analyze and explain the concept of total relationship agreement in providing credit. With the background of Bank Mandiri's policy in letter no. 033/SPb/MTF/VI/2023 this article was written to analyze the correlation of the Total Relationship Agreement concept with this policy and to analyze whether the use of the Total Relationship Agreement concept in Bank Mandiri's policy is in accordance with credit grant approval procedures or not yet. By using normative juridical research methods based on Law no. 7 of 1992 concerning Banking as amended several times, most recently by Law no. 4 of 2023 concerning Development and Strengthening of the Financial Sector and OJK Regulation no. 42/POJK.03/2017 concerning the Obligation to Prepare and Implement Bank Credit or Financing Policies for Commercial Banks, it was found that the Total Relationship Agreement concept in Bank Mandiri policy No. 033/SPb/MTF/VI/2023 was carried out to analyze the ability to pay credit applicants based on the debt conditions of the company where the prospective credit applicant works. With the issuance of Bank Mandiri policy no. 033/SPb/MTF/VI/2023 resulted in an analysis of approval for granting credit that was not in accordance with the procedures and procedures for analyzing approval for granting credit. The bank's confidence in the credit applicant's ability to pay credit must be achieved by analyzing credit approval methods. Analysis of approval for granting credit must be assessed objectively and in depth and based on the completeness of the credit applicant's files and information. With an analysis of approval for granting credit that is not based on existing assessment procedures, the analysis of approval for granting credit will have the potential to be an analysis that is not objective and in-depth. Penelitian ini bertujuan untuk menganalisis dan menjabarkan Konsep Hubungan Total (total relationship agreement) pada pemberian kredit. Dengan berlatar belakang pada kebijakan Bank Mandiri pada surat No. 033/SPb/MTF/VI/2023 artikel ini ditulis untuk menganalisis korelasi Konsep Hubungan Total (total relationship agreement) dengan kebijakan tersebut serta menganalisis apakah penggunaan Konsep Hubungan Total (total relationship agreement) pada kebijakan Bank Mandiri tersebut sudah sesuai dengan prosedur persetujuan pemberian kredit atau belum. Dengan menggunakan metode penelitian yuridis normatif dengan berlandaskan pada UU No. 7 tahun 1992 tentang Perbankan sebagaimana telah diubah beberapa kali terakhir dengan UU No. 4 tahun 2023 tentang Pengembangan dan Penguatan Sektor Keuangan dan Peraturan OJK No. 42/POJK.03/2017 tentang Kewajiban Penyusunan dan Pelaksanaan Kebijakan Perkreditan atau Pembiayaan Bank bagi Bank Umum , ditemukan bahwa Konsep Hubungan Total (total relationship agreement) pada kebijakan Bank Mandiri No. 033/SPb/MTF/VI/2023 dilakukan untuk menganalisis kemampuan membayar pemohon kredit berdasarkan kondisi hutang perusahaan tempat calon pemohon kredit bekerja. Dengan dikeluarkannya kebijakan Bank Mandiri No. 033/SPb/MTF/VI/2023 membuat terjadinya analisis persetujuan pemberian kredit yang tidak sesuai dengan prosedur dan tata cara analisis persetujuan pemberian kredit. Kepercayaan Bank terhadap Kemampuan membayar pemohon kredit dalam membayar kredit haruslah dicapai dengan metode analisis persetujuan pemberian kredit. Analisis persetujuan pemberian kredit haruslah dinilai secara objektif dan mendalam serta berdasarkan pada kelengkapan berkas dan informasi pemohon kredit. Dengan adanya analisis persetujuan pemberian kredit yang tidak berdasarkan prosedur-prosedur penilaian yang ada maka analisis persetujuan pemberian kredit tersebut berpotensi menjadi analisis yang tidak objektif dan tidak mendalam.